Breast Cancer Antiestrogen Resistance 3 (BCAR3) Promotes Cell Motility by Regulating Actin Cytoskeletal and Adhesion Remodeling in Invasive Breast Cancer Cells - Ashley Wilson; Randy S. Schrecengost; Michael S. Guerrero; Keena S. Thomas; Amy H. Bouton (2013)
Metastatic breast cancer is incurable. In order to improve patient survival, it is critical to develop a better understanding of the molecular mechanisms that regulate metastasis and the underlying process of cell motility. Here, we focus on the role of the adaptor molecule Breast Cancer Antiestrogen Resistance 3 (BCAR3) in cellular processes that contribute to cell motility, including protrusion, adhesion remodeling, and contractility. Previous work from our group showed that elevated BCAR3 protein levels enhance cell migration, while depletion of BCAR3 reduces the migratory and invasive capacities of breast cancer cells. In the current study, we show that BCAR3 is necessary for membrane protrusiveness, Rac1 activity, and adhesion disassembly in invasive breast cancer cells. We further demonstrate that, in the absence of BCAR3, RhoA-dependent signaling pathways appear to predominate, as evidenced by an increase in RhoA activity, ROCK-mediated phosphorylation of myosin light chain II, and large ROCK/mDia1-dependent focal adhesions. Taken together, these data establish that BCAR3 functions as a positive regulator of cytoskeletal remodeling and adhesion turnover in invasive breast cancer cells through its ability to influence the balance between Rac1 and RhoA signaling. Considering that BCAR3 protein levels are elevated in advanced breast cancer cell lines and enhance breast cancer cell motility, we propose that BCAR3 functions in the transition to advanced disease by triggering intracellular signaling events that are essential to the metastatic process.